NIVEL DE CONOCIMIENTO SOBRE EL PARTO HUMANIZADO EN GESTANTES QUE ACUDEN AL CENTRO DE SALUD DE PUEBLO NUEVO ENTRE OCTUBRE – DICIEMBRE DEL 2018 - HUALLANCA POCCO, KELLY NOELIA (2020)
Objective: To determine the level of knowledge about humanized childbirth in pregnant women who come to the Pueblo Nuevo Health Center between October - December 2018. Methods and techniques: The simple descriptive research method was used. The population was made up of 110 pregnant women attended. The survey was used as a technique and a questionnaire was applied as an instrument, which was validated by expert judgment. Results: Regarding the level of knowledge, 77.3% showed a regular level on the basic concepts of humanized childbirth, 86.4% high knowledge on the positions of humanized childbirth and 52.7% had low knowledge of the activities carried out during the humanized childbirth. In addition, data were collected from pregnant women on sociodemographic aspects, the predominant age was 19-35 years with 65.5%, 55.5% are cohabiting, 63.6% have a secondary level and 65.5% are a housewife. In the gyneco-obstetric aspects, we found that 55.5% have 1-3 children, 37.3% had 1-3 prenatal care (NPC) and 57.3% were in the last trimester of gestation. Conclusions: A high percentage of pregnant women with secondary education, have a basic knowledge of basic concepts; Those who have had parity in turn possess a high level of knowledge in positions regarding childbirth; and, finally, we find that they do not attend their NPCs on time and do not attend psychoprophylaxis, which results in a low knowledge of the activities carried out in humanized childbirth. Key words: Level of knowledge, humanized and pregnant childbirth.